Tourism and tourist promotion in Spain - Carsten R. Moser (Intereconomics, 1972)
The development of tourism as a big industry is a feature of the second half of the 20th century. Spain is one of the countries where tourism has made especially notable progress. While the number of foreign tourists visiting Spain amounted to only 1 mn in 1950, by 1971 it had increased to 27 mn.
Keywords: 330; Developing Countries